Linear A tablet vs. Linear B tablet - Tomas, Helena (2011)
The paper presents differences between two most prominent types of administrative documents in Linear A and Linear B. Both are called the 'clay tablet', but despite their identical names, notable differences are observed in the sphere of pinacology and epigraphy, which leads us to believe that they played different administrative roles.
Projekt MZOS
ENG